The Influence of the Guided Inquiry Learning Model on the Critical Thinking Skills of Fifth-Grade Students in Social Studies Subjects - Haedi, Ismayanti; Jamaludin, Ujang; Taufik, Muhammad (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
The success of social studies learning is strongly influenced by the ability of teachers to provide critical thinking skill in the learning process activities. This research aimed to (1) determine the influence of the guided inquiry learning model on fifth-grade students' critical thinking skills in social studies subjects and (2) find out whether there are differences in fifth-grade students' critical thinking skills after applying the guided inquiry learning model and the direct instruction model. The research method applied quasi-experimental. The research design was a nonequivalent control group design. Data collection techniques used both test and non-test. The results highlighted the influence of guided inquiry learning models on fifth-grade of the State Elementary School of  Taman Baru 2 students' critical thinking skills and differences in students' critical thinking skills before and after applying the guided inquiry learning model. Moreover, the post-test mean was more significant than the pre-test, 83.89 49.47. The paired samples t-test also revealed that the sig. value of pair 1 was 0.000 0.05, and the sig. value of pair 2 was 0.000 0.05. Further, the mean experimental post-test was higher than the control post-test, 83.89 71.89. The independent samples t-test also obtained the sig. value (2-tailed) of 0.002 0.05. Hence, learning was more successful or influential through the guided inquiry learning model on the critical thinking skills of fifth-grade students in social studies subjects.